(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the role of oral verses IV antibiotics in patients with spontaneous bacterial peritonitis. Study Design: Randomized trial study. Place and Duration of Study: This study was conducted at the Department of Medicine, Services hospital, Lahore from June 2017 to December 2017. Materials and Methods: Patients of age range 16-80years of either gender with SBP due to cirrhosis were included. Patients with other comorbidities like varices, previous failed medical management or recurrent SBP were excluded. Then patients were randomized in either group and treatment was given. Patients were followed-up and presence of SBP and mortality was noted. Results: The mean age of patients was 45.36±12.02years in oral group and 46.67±11.94years in IV group. There were 37 males and 13 females in oral group while 28 males and 22 females in IV group. SBP was eradicated in 43 (86%) patients with oral antibiotics while in 46 (92%) patients with IV antibiotics. Mortality occurred in 1 (2%) patients with oral antibiotics while in 1 (2%) patients with IV antibiotics. The difference was insignificant (p>0.05). Conclusion: The role of both oral and intravenous antibiotic are equal in eradication of spontaneous bacterial peritonitis. Thus we can replace IV antibiotics with oral antibiotics and can improve compliance.